2019
DOI: 10.3389/fpls.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Study of the ANT Family Points to a preANT Gene as the Ancestor of Basal and euANT Transcription Factors in Land Plants

Abstract: Comparative genomics has revealed that members of early divergent lineages of land plants share a set of highly conserved transcription factors (TFs) with flowering plants. While gene copy numbers have expanded through time, it has been predicted that diversification, co-option, and reassembly of gene regulatory networks implicated in development are directly related to morphological innovations that led to more complex land plant bodies. Examples of key networks have been deeply studied in Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…TaAP2/ERF gene family is supposed to have a critical role in signal transduction and transcriptional adjustment because most of the genes of this family are predicted to be present in the nucleus as compared with T. durum which is a close relative to T. aestivum Figure 5B ( Faraji et al, 2020 ). As it is clear from the previous results that AP2/ERF gene family plays a critical role in plant growth and development ( Scheres and Krizek, 2018 ; Dipp-álvarez and Cruz-Ramírez, 2019 ; Jiang et al, 2019 ; Wang et al, 2019 ). So, our study about AP2/ERF genes in wheat will be useful for improving the wheat crop from different biotic and abiotic stresses in the future.…”
Section: Discussionmentioning
confidence: 85%
“…TaAP2/ERF gene family is supposed to have a critical role in signal transduction and transcriptional adjustment because most of the genes of this family are predicted to be present in the nucleus as compared with T. durum which is a close relative to T. aestivum Figure 5B ( Faraji et al, 2020 ). As it is clear from the previous results that AP2/ERF gene family plays a critical role in plant growth and development ( Scheres and Krizek, 2018 ; Dipp-álvarez and Cruz-Ramírez, 2019 ; Jiang et al, 2019 ; Wang et al, 2019 ). So, our study about AP2/ERF genes in wheat will be useful for improving the wheat crop from different biotic and abiotic stresses in the future.…”
Section: Discussionmentioning
confidence: 85%
“…The conserved AP2 DNA binding domains of amino acids 57-66 characterize the AP2/ERF superfamily [ 41 ]. In accordance with the double AP2 domain amino acid sequence and the nuclear location sequence, the AP2 family was subdivided into euAP2, eu-AINTEGUMENTA (euANT) and basalANT groups, respectively [ 42 , 43 , 44 ]. AP2 TFs play a number of roles in plant developmental processes and stress responses, such as vegetative and reproductive growth, cell proliferation, abiotic and biotic stress responses, and plant hormone responses [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence showed that AP2 family genes play pivotal roles in regulating plant growth and development (Scheres and Krizek, 2018; Dipp-Alvarez and Cruz-Ramirez, 2019; Jiang et al, 2019; Wang et al, 2019a). Arabidopsis AtANT was one of the first genes in the family that were functionally characterized; it regulates organ size, floral meristem patterning, and plant defense pathways (Elliott et al, 1996; Krizek et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The AP2 family proteins contain two repeated AP2 domains; the ERF family proteins contain a single AP2 domain; the RAV (related to ABI3/VP1) family proteins contain two different DNA binding domains, AP2 and B3 (Sakuma et al, 2002; Nakano et al, 2006). The AP2 family was subdivided into the euAP2, eu-AINTEGUMENTA (euANT) and basalANT groups according to the amino acid sequence of the double AP2 domain and the nuclear localization sequence (Shigyo et al, 2006; Wang et al, 2016a; Dipp-Alvarez and Cruz-Ramirez, 2019).…”
Section: Introductionmentioning
confidence: 99%